Characterization of two Kaposi's sarcoma cell lines and their response to chemotherapeutic agents. - Payette, Paul J. (University of Ottawa (Canada), 1998)
Kaposi's sarcoma (KS) is a multifocal proliferative disorder that is commonly associated with individuals who suffer some degree of reduction in immune competence. Therapy for this disorder varies and is determined by the seriousness of KS disease in the patient as well as the patient's ability to tolerate the different treatments. A better understanding of how KS arises would allow investigators to tailor therapies that would be more specific to KS and less detrimental to the individual. In this work, cell lines were established from skin biopsies taken from KS lesions of individuals with AIDS. The KS1 cell line presented as a combination of adherent and non-adherent cells that proliferated aggressively without senescence. The KS4 cell line presented as the typical spindle cell population that proliferated aggressively, but eventually senesced. Both cell lines were positive for the presence of Factor VIII-related antigen (FVIII) and the production of IL-6 and basic Fibroblastic Growth Factor (bFGF). When the association with Human Herpesvirus 8 (HHV8) was assessed, the virus proved undetectable in both cell lines. The response of the KS cell lines to Doxorubicin, Etoposide, and ALX40-4C was assessed. (Abstract shortened by UMI.)
Keywords: Health Sciences, Oncology.